2023
DOI: 10.1007/s11356-023-25579-4
|View full text |Cite
|
Sign up to set email alerts
|

Diesel particulate filter regeneration mechanism of modern automobile engines and methods of reducing PM emissions: a review

Abstract: Diesel particulate filter (DPF) is considered as an effective method to control particulate matter (PM) emissions from diesel engines, which is included in the mandatory installation list by more and more national/regional laws and regulations, such as CHINA VI, Euro VI, and EPA Tier3. Due to the limited capacity of DPF to contain PM, the manufacturer introduced a method of treating deposited PM by oxidation, which is called regeneration. This paper comprehensively summarizes the most advanced regeneration tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 259 publications
1
14
0
Order By: Relevance
“…DPF regeneration is a method of removing the accumulated PM from the filter material. 73 The present study demonstrated an apparent effect in the emissions and the toxicological endpoints with the active DPF regeneration event. During the active regeneration, the accumulated soot particulates are burned from the filter by adding excess fuel in the exhaust gas system, increasing the temperature to 600 °C, followed by a multi-fold increase in PM emissions.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…DPF regeneration is a method of removing the accumulated PM from the filter material. 73 The present study demonstrated an apparent effect in the emissions and the toxicological endpoints with the active DPF regeneration event. During the active regeneration, the accumulated soot particulates are burned from the filter by adding excess fuel in the exhaust gas system, increasing the temperature to 600 °C, followed by a multi-fold increase in PM emissions.…”
Section: Discussionsupporting
confidence: 48%
“…The active regeneration event has been calculated to increase the overall particulate emissions from modern diesel vehicles and may lead to an underestimation of real-world PM emissions. 73 DPF regeneration events have also been associated with an increase in sulphur emissions, 74 , as seen in the results of Saarikoski et al , 2023. 36 Moreover, the recent light-duty vehicle emissions regulations do not include the emissions spikes during filter regeneration.…”
Section: Discussionmentioning
confidence: 80%
“…This paper provides a better understanding of the relationship between EGR, biodiesel blending ratio, and load on the biodiesel engine, and provides a reference for future research on the parameters of biodiesel engines and the development of EGR systems. In future work, more engine parameters and more efficient and refined optimization methods will be considered (Zhang et al, 2023b).…”
Section: Discussionmentioning
confidence: 99%
“…Diesel engines are preferred because of their power production, availability of current technology, low operating costs, and dependability . Diesel engine exhaust in the atmosphere wreaks havoc on the ecosphere and creates a variety of health problems . Environmental degradation and global warming are brought on by inefficient combustion of fossil fuel combustion.…”
Section: Introductionmentioning
confidence: 99%